Exploring Geometric Comprehension Patterns of Elementary School Students Based on Gender through Pirie-Kieren Theory in the Context of Mande Culture in Malang Semirang - Novia Hasna Fuadah; Dina Pratiwi Dwi Santi; setiyani (PT. Global Research Collaboration, 2026)
Understanding geometry is an important aspect of elementary mathematics learning, yet many students still experience difficulties in understanding geometric concepts. This study aims to describe elementary school students' geometric understanding based on gender through the Pirie–Kieren theory in the context of Mande Malang Semirang and to identify the scaffolding required at each layer of understanding. This study employed a qualitative case study approach involving four high-achieving fifth-grade students, consisting of two male and two female students selected through purposive sampling. Data were collected through geometry understanding tests, observations, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings showed that all participants achieved the eight layers of understanding proposed by the Pirie–Kieren theory. However, differences were observed in their thinking processes and folding-back patterns. Male students tended to rely on concrete experiences and visual observations, whereas female students demonstrated more systematic reasoning supported by mental visualization. These findings suggest that the scaffolding required may vary among learners, highlighting the importance of considering gender as one of several factors in designing ethnomathematics-based geometry learning.